Origin and Composition of Cell-Free DNA in Spent Medium From Human Embryo Culture During Preimplantation Development. Issue 6 (June 2018) - Vera-Rodriguez, M.; Diez-Juan, A.; Jimenez-Almazan, J.; Martinez, S.; Navarro, R.; Peinado, V.; Mercader, A.; Meseguer, M.; Blesa, D.; Moreno, I.; Valbuena, D.; Rubio, C.; et al.
Abstract : (Abstracted from Human Reprod 2018;33:745–756) Chromosomal aneuploidy is common. It occurs in 20% to 80% of human embryos.